2005
DOI: 10.1021/om050156d
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Phosphino-Iminolate Complexes as Metalloligands for Coinage Metals:  A Versatile, Ambivalent Behavior

Abstract: Reactivity studies with the bis-chelated Pd(II) phosphino-iminolate complex [Pd(dmba)(κ2-P,O-PPh2NC(O)Me)] (2) (dmba = orthometalated dimethylbenzylamine) have shown that it readily reacts as a metalloligand with electrophilic complexes of the coinage metals, selectively via the nitrogen atom of the P,O chelate. After examining its reaction with AgOTf (OTf = SO3CF3), which afforded the first 1-D coordination polymer containing Ag−Pd bonds, [{Ag(2)}OTf] n (3·OTf), we have examined and compared its reactions wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Previous work has shown that transition metal complexes containing a phosphino-enolate or iminolate function react with electrophilic metal centres at the C enolate or N iminolate atoms, respectively, leading to heterometallic complexes and unique coordination polymers. 3,20, 21 The complexes reported in this work, therefore represent interesting candidates to extend such studies.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Previous work has shown that transition metal complexes containing a phosphino-enolate or iminolate function react with electrophilic metal centres at the C enolate or N iminolate atoms, respectively, leading to heterometallic complexes and unique coordination polymers. 3,20, 21 The complexes reported in this work, therefore represent interesting candidates to extend such studies.…”
Section: Discussionmentioning
confidence: 72%
“…3 The replacement of the PCH 2 group of such ketophosphines with an isoelectronic PNH group in amide-derived ligands, or of the PCH functionality of phosphinoenolates with a PN group in iminolate phosphines, can bring about very interesting electronic and geometric effects in their respective metal complexes. 3,17- 21 Here, we report the synthesis and characterization of Co(III) and Ni(II) complexes containing the neutral b-ketophosphine ligands (i-Pr) 2 PCH 2 C(O)Ph (HL 1 ) and Ph 2 PCH 2 C(O)Ph (HL 2 ) 22 or the acetamide-derived phosphine ligand (i-Pr) 2 PNHC(O)Me (HL 3 ), prepared similarly to Ph 2 PNHC(O)Me (HL 4 ), 18 or the deprotonated form of these ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Except for its X-ray structures obtained in pure form under high pressure (Podsiadlo et al, 2005) and very low temperature (Kawaguchi et al, 1973), the Cambridge Structural Database contains fewer than ten complexes comprising type II ClÁ Á ÁCl halogen bonds between CH 2 Cl 2 molecules. Hereafter are provided the CSD reference codes of structures containing type II contacts between CH 2 Cl 2 molecules, considering the following crystallographic parameters C-Cl1Á Á ÁCl2 and Cl1Á Á ÁCl2-C angles in the ranges 150-180 and 70-110 , respectively, and Cl1Á Á ÁCl2 distances in the range 2.5-3.6 Å : FAHGON (Kubota et al, 2016), HIQDUI (Kenny et al, 2013), REGTED (Pasynskii et al, 2005), YIHKAD (Nishimura et al, 2013), OZIJUE (Raducan et al, 2011), PAQTAD (Oberbeckmann-Winter et al, 2005), TIYQOJ (Wang et al, 2013). In these structures, the halogen bonds are present as part of a more elaborate network between CH 2 Cl 2 molecules, forming two-dimensional sheets or one-dimensional propagating ribbons.…”
Section: Interaction Energies and Electrostatic Potential Mapsmentioning
confidence: 99%
“…www.chemeurj.org in the heterodimetallic product. This procedure has been used previously, [11] for example, with…”
Section: Reactivity Of the Ptmentioning
confidence: 99%